The Bay and Padie book : kiddie songs - Maurice, Furnley, 1881-1942.; Dobbs, Cyril; Hamilton, Vera. (Melbourne : Sydney J. Endacott, 1917)
Poems of life and adventure, centred mainly on two small sons, Bay and Paddie.
Libraries HHP 5529 copy inscribed in black ink, "With love to the "Woman" from Lady Spen. Xtmas 1918." on first free end paper; additional inscription in black ink dated 27/12/17 to Father Bard opposite title page; also signed in blue ink on the title page by Sydney J. Endacott.
Muir, M. A bibliography of Australian children's books
For children.
Also available online
Keywords: Children -- Poetry; Children's poetry, Australian; Parent and child -- Poetry